Digitalisasi Pelaporan Keuangan dengan Aplikasi Akuntansi untuk Meminimalisasi Potensi Terjadinya Fraud - Putra, Yananto Mihadi; Irwan, Irwan; Monalisa, Dina; Adiandari, Ade Maharini (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2025)
This financial reporting digitalization training with accounting applications aims to reduce the risk of fraud in the financial reports of small and medium enterprises and young entrepreneurs. The main problem is the low understanding of participants in making accurate and transparent digital financial reports. The activity partners are students of SMKN 25 Jakarta who need to improve their skills in preparing application-based financial reports such as BukuWarung, SIAPIK, and Accurate. Training methods include observation, socialization, practice of using applications according to financial accounting standards, mentoring, and evaluation. The training lasted for 16 hours with theoretical and practical materials. The evaluation results showed a significant increase in participant understanding and readiness to apply accounting technology in an accountable manner. Obstacles such as limited technological facilities and variations in participant abilities were overcome by rescheduling and special mentoring. Recommendations for this activity include improving technological facilities, developing flexible learning materials, and ongoing mentoring so that the benefits of the training can continue. This activity also supports the implementation of the Merdeka Belajar Kampus Merdeka program through the active role of students as facilitators.